A RANDOMIZED CONTROLLED TRIAL OF JIGSAW VERSUS E-LEARNING APPROACHES: PRACTICAL PARASITOLOGY TRAINING TO IMPROVE PARASITE IDENTIFICATION TECHNIQUES IN CLINICAL LABORATORY SCIENCE EDUCATION - Kobayashi, Koji; Yuuko Kosuge; Akazawa, Kohei (Asian Journal Of Medical Technology, 2023)
Japan is witnessing an increase in parasitic diseases caused by contaminated food, international travel, and sexual activity, but much less time is spent on parasitology education. To avoid incorrect identifications, students were required to master the technique in a limited amount of time. This requirement necessitates new and more effective teaching methods that allow students to identify parasites. In this study, we conducted practical parasitology training using two teaching methods. We assigned 33 students to the jigsaw method (class A) and another 33 to the e-learning method (class B). This study aimed to determine the effectiveness and limitations of these teaching methods. Therefore, we conducted an RCT to reduce confounding bias and increase the validity of our results. The primary outcome was the participants’ scores in the microscopic test to identify helminth eggs and protozoa in faecal and blood specimens, while the secondary outcome was the participant’ scores in the photo test. The results showed that the median scores for the microscopic test were 83.3 for class A and 91.6 for class B (p = 0.085), and the mean scores for the photo test were 79.4 for class A and 87.3 for class B (p = 0.033). Therefore, the e-learning method was more effective than the jigsaw method.